Gas-to-power market and investment incentive for enhancing generation capacity – an analysis of Ghana’s electricity sector - Fritsch, J; Poudineh, R (Oxford Institute for Energy Studies, 2015)
Ghana’s electricity generation capacity is currently insufficient to meet demand, making power outages and load shedding common. The resulting impact is potentially devastating for the country’s growth prospects. Traditionally, lack of an affordable and reliable fuel supply for power generation, coupled with ineffective institutions and an unfavourable investment climate, have resulted in Ghana’s electricity sector performing poorly. In light of the 2007 discovery of natural gas reserves in Ghanaian waters, this paper examines whether domestic gas could advance the performance of the electricity sector, and if so, how. The results of our analysis show that utilization of gas reserves in Ghana’s gas-to-power market is an economically superior strategy compared to an export-oriented utilization scheme. The lack of an effective regulatory framework for investment, skill shortages, and an inefficient electricity pricing structure continue to be the main constraining factors. Our analysis also considers possible approaches to modification of the electricity tariff in order to send the right signal to potential investors in generation capacity, without compromising the affordability of power supply.